AN UPDATE OF THE GENUS ETLINGERA (ZINGIBERACEAE) IN SULAWESI INCLUDING THE DESCRIPTION OF A NEW SPECIES - Ardiyani, Marlina; Poulsen, Axel Dalberg (Research Center for Biology, 2019)
ARDIYANI, M. & POULSEN, A. D. 2019. An update of the genus Etlingera (Zingiberaceae) in Sulawesi including the description of a new species. Reinwardtia 18(1): 49?60. ? A new species, Etlingera mamasarum A.D.Poulsen & Ardiyani was discovered in Gunung Gandangdewata National Park, West Sulawesi. It is similar to Etlingera flexuosa A.D.Poulsen but differs in having flowers which are shorter than the bracts. It is described, illustrated and DNA barcoded. Three additional species (Etlingera cylindrica A.D.Poulsen, E. grallata A.D.Poulsen, E. spinulosa A. D.Poulsen) were documented in this national park and represent new records for West Sulawesi Province. We also update information on the morphology of E. calobates A.D.Poulsen, correct an error in the typification of Alpinia chrysogynia (K.Schum.) K.Schum. and discuss the distribution of the Achasma Group of Etlingera east of Wallace?s Line.